Original Short Stories $1 (BVolume 11s - Maupassant, Guy de, 1850-1893; Henderson, A. E.; McMaster, Albert Cohn; Quesada, Louise Charlotte Garstin (Salt Lake City, UT : Project Gutenberg, 2004)
"Original Short Stories $1 (BVolume 11" by Guy de Maupassant is a collection of short stories written in the late 19th century. This volume contains a diverse array of tales, showcasing the author's keen observations of human behavior and social intricacies, often with a touch of irony or dark humor. The stories explore themes of domestic life, societal norms, and personal struggles, centering around a cast of relatable characters such as the economical Mme. Oreille and her husband Oreille in "The Umbrella". At the start of "The Umbrella," readers are introduced to Mme. Oreille, a frugal woman who carefully manages her finances, much to the chagrin of her husband, Oreille. He endures her tight-fisted nature regarding expenses, particularly when it comes to his old umbrella, which he feels embarrassed to take to work. Tired of mockery from his colleagues, he insists on a new umbrella, leading to a series of arguments when it becomes damaged. The opening paints a vivid picture of their domestic strife, defined by a mix of humor and escalating tension, as the couple navigates the repercussions of spending and the pressures of marital expectations. This exploration sets the tone for the subsequent stories in the collection, each capturing the complexities of everyday life with Maupassant's characteristic wit. (This is an automatically generated summary.)s
The umbrella -- Belhomme's beast -- Discovery -- The accursed bread -- The dowry -- The diary of a mad man -- The mask -- The penguins rock -- A family -- Suicides -- An artifice -- Dreams -- Simon's papa.
Release date is 2004-10-03
Produced by David Widger
Keywords: Short stories, French -- Translations into English